Loop-Mediated Isothermal Amplification Method for the Rapid Detection of Ralstonia solanacearum Phylotype I Mulberry Strains in China - Huang, Wen; Zhang, Hao; Xu, Jingsheng; Wang, Shuai; Kong, Xiangjiu; Ding, Wei; Xu, Jin; Feng, Jie (Frontiers in Plant Science, 2017)
Ralstonia solanacearum phylotype I mulberry strains are causative agent of bacterial wilt of mulberry. Current diagnostic methods are not adopted to the mulberry wilt disease. In this study, we developed a rapid method, loop-mediated isothermal amplification (LAMP), to detect R. solanacearum phylotype I mulberry strains. A set of six primers was designed to target the clone MG67 sequence in this LAMP detection which can be completed in 20 min at 64 °C. The results of the LAMP reaction could be observed with the naked eye due to magnesium pyrophosphate precipitate produced during the reaction or the color change after adding SYBR Green I. The specificity of the LAMP was confirmed using DNA from 46 representative strains of R. solanacearum and 7 other soil-borne bacteria strains. This method was also of high sensitivity and could be used to detect the presence of less than 160 fg genomic DNA or 2.2×102 CFU/ml of bacterial cells per 25 μl reaction volume, moreover, the presence of plant tissue fluid did not affect the sensitivity. Since it does not require expensive equipment or specialized techniques, this LAMP-based diagnostic method has the potential to be used under field conditions to make disease forecasting more accurate and efficient.